2009
DOI: 10.1016/j.jala.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a Fully Automated Molecular Diagnostics System

Abstract: Molecular diagnostics presents challenges to clinical laboratories that are under pressure to consolidate and automate. There is a need to evaluate molecular automation for process efficiency and suitability for high-throughput environments in core laboratories. A fully automated molecular instrument platform (the BD Viper System with XTR Technology in extracted mode [BD Viper System with XTR]), was evaluated for automation efficiency, labor requirements, and system robustness. System productivity was predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This higher time measurement is consistent with the measurement determined by Felder et al 5 ''Hands-on'' timing measurements in the Extracted Mode were relatively consistent between both institutions and ranged between 29.8 and 34.2 min. There was a 5.8e7.9-min increase in the total amount of ''hands-on'' time necessary for processing swabs in the Extracted Mode compared with Nonextracted Mode at both testing facilities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This higher time measurement is consistent with the measurement determined by Felder et al 5 ''Hands-on'' timing measurements in the Extracted Mode were relatively consistent between both institutions and ranged between 29.8 and 34.2 min. There was a 5.8e7.9-min increase in the total amount of ''hands-on'' time necessary for processing swabs in the Extracted Mode compared with Nonextracted Mode at both testing facilities.…”
Section: Discussionsupporting
confidence: 90%
“…Eluate is then neutralized to buffer conditions optimal for real-time amplification, achieved by SDA. 5 There were two objectives in this study design: to measure the time-related efficiencies of the Viper XTR in Extracted Mode to that in Nonextracted Mode in terms of overall ''hands-on'' time and total processing time (TPT), and to correlate the accuracy of performance of Viper XTR in Extracted Mode to Nonextracted Mode at spike levels of CT and GC organisms indicative of low analytical loads of these pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…There are few timemotion studies reported in the literature that have evaluated the characteristics of these new platforms, particularly for CT/NG testing. [3][4][5][6][7] Head-to-head evaluations that assess multiple systems using a standardized approach provide critical information to laboratories considering adoption of a new platform. In this study, four automated systems routinely used for the detection of CT/NG were assessed for total run time, hands-on and available walk-away time associated with a run, and ease of instrument set up, operation, and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…With clearance by the U.S. Food and Drug Administration and other regulatory agencies in Europe and elsewhere of several systems, automated molecular testing has become routine in clinical laboratory practice, ensuring diagnostic accuracy and improved result turnaround time (TAT). Studies have been published assessing clinical performances of molecular assays (2)(3)(4)(5)(6)(7)(8), and workflow and maintenance characteristics of automated instruments (9)(10)(11)(12)(13)(14)(15)(16). In addition to performance and instrumentreagent costs, hands-on time required for testing and maintenance, in-process interaction, and time to results and test capacity are key metrics that should be considered because they can influence efficiency and labor costs.…”
mentioning
confidence: 99%